Psychosocial correlates of overweight and obesity in infancy - Gonçalves, Sónia (2012)
Obesity is a complex disease with not only physical consequences but also psychological. The aim of the present work was to analyze differences between community children with normal weight versus community overweight children versus children with overweight in clinical setting, at the level of quality of life, psychological morbidity and self-concept . The study sample has 267 children represented in three groups: group of community children with normal weight (N = 147), group of community overweight children (N = 89) and a group of overweight children in treatment (N = 31). The results from this study showed differences on quality of life, for the total scale and on the dimension of physical health and school health, in which overweight children in the clinical sample are the ones who presented more negative perception of physical health and school health, when compared with community children with normal weight vs community overweight children. For the rest of the dimensions of quality of life, no significant differences were found between the three groups. Regarding the self-concept on the group of children with a clinical diagnosis of obesity they perceived themselves as less competent relative to school competency, athletic competency, physical appearance, social acceptance, behavior and self-esteem. Regarding the variable depression this study suggests that community overweight children present more depressive symptomatology when compared with the other groups. No significant differences were found regarding anxiety symptomatology. To summarize, results from this empirical study demonstrated the importance of psychological variables when in the presence of obesity.